2022
DOI: 10.15388/amed.2021.29.1.7
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Epigenetic Changes in Vitamin D Pathway Genes in Rheumatoid Arthritis Patients

Abstract: Background: Rheumatoid arthritis (RA) is an autoimmune inflammatory disease with complex etiopathogenesis launched by multiple risk factors, including epigenetic alterations. RA is possibly linked to vitamin D that is epigenetically active and may alter DNA methylation of certain genes. Therefore, the study aimed to evaluate the relationship between DNA methylation status of vitamin D signaling pathway genes (VDR, CYP24A1, CYP2R1), vitamin D level and associations with RA.Materials and Methods: Totally 76 part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…The study identified a significant reduction of VDR methylation levels in RA patients compared to CTRs, suggesting that this signature may represent a potential disease biomarker [23]. In contrast with these results, a second epigenetic study revealed no significant differences in the methylation levels of 10 CpG sites within the VDR primary promoter between a group of 35 RA patients and 41 healthy subjects [19]. However, this controversial result could be attributed to both the small size of the study cohort and the small number of CpG sites analyzed.…”
Section: Autoimmune Diseasesmentioning
confidence: 64%
See 1 more Smart Citation
“…The study identified a significant reduction of VDR methylation levels in RA patients compared to CTRs, suggesting that this signature may represent a potential disease biomarker [23]. In contrast with these results, a second epigenetic study revealed no significant differences in the methylation levels of 10 CpG sites within the VDR primary promoter between a group of 35 RA patients and 41 healthy subjects [19]. However, this controversial result could be attributed to both the small size of the study cohort and the small number of CpG sites analyzed.…”
Section: Autoimmune Diseasesmentioning
confidence: 64%
“…The function of the vitamin D is mediated by its binding with VDR on the membrane of immune system cells such as dendritic cells, monocytes and B and T lymphocytes [17]. Consequently, the genetic variability and epigenetic modifications in the VDR could alter immune homeostasis, significantly impacting the onset and progression of autoimmune diseases, such as Rheumatoid Arthritis (RA), Multiple Sclerosis (MS) and Behcet's Disease (BD) (Table 1) [18][19][20][21]. RA is a progressive autoimmune disease characterized by chronic joint inflammation and pain, attributed to the influx of CD4+ TCs into the synovial lining and the increase of macrophage-like and fibroblastlike cells that produce degradative enzymes and proinflammatory cytokines [22].…”
Section: Autoimmune Diseasesmentioning
confidence: 99%
“…The study identified a significant reduction in the VDR methylation levels in RA patients compared to CTRs, suggesting that this signature may represent a potential disease biomarker [ 26 ]. In contrast with these results, a second epigenetic study revealed no significant differences in the methylation levels of 10 CpG sites within the VDR primary promoter between a group of 35 RA patients and 41 healthy subjects [ 22 ]. However, this controversial result could be attributed to both the small size of the study cohort and the small number of CpG sites analyzed.…”
Section: Autoimmune Diseasesmentioning
confidence: 98%
“…The function of the 1,25(OH) 2 D 3 is mediated by its binding with the VDR on the membrane of immune system cells such as dendritic cells, monocytes, and B and T lymphocytes [ 20 ]. Consequently, the genetic variability and epigenetic modifications in the VDR could alter immune homeostasis, significantly impacting the onset and progression of autoimmune diseases, such as rheumatoid arthritis (RA), multiple sclerosis (MS), and Behcet’s disease (BD) [ 21 , 22 , 23 , 24 ]. RA is a progressive autoimmune disease characterized by chronic joint inflammation and pain, attributed to the influx of CD4+ TCs into the synovial lining and the increase in macrophage-like and fibroblast-like cells that produce degradative enzymes and proinflammatory cytokines [ 25 ].…”
Section: Autoimmune Diseasesmentioning
confidence: 99%
“…In addition, epigenetic signatures, including DNA methylation, seem to modulate VDR gene expression and appear intensely involved in bone diseases [ 26 , 27 ]. In this context, higher vitamin D concentration was shown to be associated with higher VDR promoter methylation in rheumatoid arthritis (RA) patients [ 28 ]. Interestingly, recent data suggest a link between Cdx2 genotype-specific VDR expression and differential VDR methylation, regardless of ethnicity [ 12 ], supporting the complex interaction between genetics, epigenetics and environment in OP pathogenesis.…”
Section: Introductionmentioning
confidence: 99%